Application of technology for effective and safe pregnancy care - Khonboon, Ronnachai (Disease Control Journal, 2025)
Proper and timely care of pregnant women, who typically experience numerous physiological changes, including fetal growth and development during gestation can mitigate the risk of gestational diabetes, hypertension, and premature birth. Currently, caring of pregnant women still encounters numerous problems, including barriers to medical services and economic and societal limitations. To address these ongoing issues, technological advancements have been implemented to support the care of pregnant women. These include telemedicine, health applications, and artificial intelligence (AI). This article aims to look at the importance and roles of technology in maternity care, both normal and complicated pregnancy, as well as the pros and cons of using it. Additionally, it analyzes opportunity and challenges in implementing those technologies. It is also intended to offer ways to use technologies effectively and safely to improve healthcare. The article utilizes a narrative review methodology and thematic analysis to investigate pertinent materials. To provide better care to mothers, nurses need to learn about new technologies, make sure that they are safe and appropriate, effectively incorporate these new technologies into traditional medical procedures and practices, and make it easier for people to share information while sending out alerts for problems identified by technology-based tools and instruments.